Vulnerability and welfare: Findings from the third round of the Myanmar Household Welfare Survey (July and August 2022) - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
The third round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between July and August 2022. It followed from a second round that was conducted between April and June 2022 and a first round that was carried out between December 2021 and February 2022. This report discusses the findings from the third round related to shocks, coping strategies, and income poverty. During the third round of data collection, the security situation in Myanmar continued to decline. Increasingly, households felt insecure in their communities, as reported by 21 percent of rural households and 25 percent of urban households, an increase compared to previous rounds. This is because crime and violence continued to increase, affecting 10 and 8 percent of communities, respectively. Further, 6 percent of households were directly affected, either through violence against a household member, robbery, or appropriation and/or destruction of their assets. Households also continued to earn less income. In July and August of 2022, 46 percent of households reported lower income compared to the previous year. Disruptions in banking, internet, and electricity also negatively impact household wellbeing and livelihoods. Further, households struggled to receive medical services. Finally, while school attendance recovered, it was still under 50 percent in some states/regions. Eighty-two percent of households used at least one coping strategy to meet daily needs during the month prior to the third-round survey. The three most common coping strategies used were spending savings, reducing non-food expenditure, and reducing food expenditure. Further, some households exhausted some or all of their coping strategies. Finally, income poverty increased during the third round; 62 percent of households were income poor. Casual wage earning and asset poor households were particularly vulnerable. Compared to the other states/regions, households in Kayah and Chin were the most vulnerable. They were more likely to be impacted by conflict, have income loss, and be income poor. Households in Rakhine, Kachin, and Tanintharyi were also vulnerable; more than 70 percent of households in those regions were income poor.